The Right to Digital Tranquility: A Comparative Analysis of AI Governance in Oman and Jordan from an Islamic Legal Perspective - Murtada Abdalla Kheiri; Racem Gassara; Nizar Qashta; Mohammed Elsadig Abdallah Mohammed Zain (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
The development of artificial intelligence (AI) and digital technology in the Middle East has raised new challenges to the right to privacy and tranquility of individuals in cyberspace. This article examines the concept of the right to digital tranquility through a comparative analysis of legal policies in the Sultanate of Oman and the Hashemite Kingdom of Jordan. This study uses a qualitative legal approach that combines normative and comparative analysis to assess the extent to which both countries regulate the collection and processing of personal data, as well as respond to digital violations arising from the use of AI. The results show that Oman implements a preventive approach based on al-siyāsah al-shar‘iyyah values with a focus on explicit user consent as stipulated in Personal Data Protection Law No. 6 of 2022. In contrast, Jordan takes a repressive and law enforcement approach through Cybercrime Law No. 17 of 2023 and Data Protection Law No. 24 of 2023, which emphasize accountability and balance between digital freedom and national security. From an Islamic legal perspective, the right to digital tranquility represents the implementation of maqāṣid al-shariah, specifically ḥifẓ al-‘ird (protection of honor) and ḥifẓ al-nafs (protection of life). Principles such as karāmah al-insān, dar’ al-mafsadah, maslahah mursalah, and lā ḍarar wa lā ḍirār form the moral basis for fair and humane AI governance. This article concludes that strengthening the right to digital peace requires an ethical, participatory AI governance model that is in line with Islamic legal values so that technological progress does not sacrifice human dignity in the digital age.